English songs in support of the linguistic development of elementary students in Finland - Holma, Veikka (2023)
In this thesis, I will discuss how music supports language learning in elementary school students, specifically learning English as a second language in Finland. I will discuss a child’s development and how language learning relates to that, music’s potential as a pedagogical tool in language education, and how the aforementioned is recognized in the national primary education curriculum. This thesis is a literature review, in which I will review previous research, articles, and books on the topic.